Odpowiedzi

2010-03-07T20:02:39+01:00
A) 2a-b dla a=-4 b=½
2 * (-4) - ½ = -8 - ½ = -8½

b) ⅗ p+½ q dla p=-25 q= -⅓
⅗ * (-25) + ½ * (-⅓) = -15 + (-⅕)= -15⅕

c)(2m-3n)² dla m=-1 n=-5
(2*(-1) - 3*(-5))²= ((-2)-(-15))² = 13² = 169


e) (⅓a+3b)(-2) dla a=-6 b=⅓
(⅓*(-6) +3 * ⅓) * (-2) = ( -2 + 1 ) * (-2) = 2

Najlepsza Odpowiedź!
2010-03-07T20:29:08+01:00
A) 2a-b=2×(-4)-½=-8-½=-4
b)p+½q=-25+½×(-⅓)=-25+(-1\6)=-25 1\6
c) (2m-3n)²=(2×(-1)-3×(-5))²=(-2+15)²=13² czyli 169
e) (⅓a+3b)(-2)=(⅓×(-6)+3×⅓)×(-2)=(-2+1)×(-2)=-1×(-2)=2
f) m²+2mn ×4n=-2²+2×(-2)×(-½)×4×(-½)=4+(-4)×(-½)×4×(-½)=4+2×4×(-½)=4+8×(-½)=4+(-4)=0